The Implementation of Mindfulness-Based Programs in the Swedish Healthcare System-A Qualitative Study - Susanne Andermo PhD; Rebecca Crane PhD; Maria Niemi PhD (SAGE Publishing, 2021)
Background: As the provision of Mindfulness-Based Programs (MBPs) in health care settings progresses, more research is needed to develop guidelines and structures for implementation in various contexts. This study is part of a larger project were MBP provision in Sweden is explored. Objective: The objective is to provide knowledge for the next steps of MBP implementation both in Sweden and internationally. The specific aim of the study is to explore how MBP teachers and other relevant stakeholders experience the implementation of MBP. Methods: Qualitative in-depth interviews were conducted with 15 MBP providers and 2 other stakeholders from a range of health care settings in Sweden. Results: The results, presented in 3 themes, provide insights into the factors that are crucial for facilitating or hindering MBP implementation; (1) MBP teachers and their training, including the importance of champion individuals and the benefit and shortcomings of various forms of MBP; (2) Patients and patient referrals, including patient characteristics and referral pathways; (3) Organizational prerequisites to successful implementation, highlighting the importance of financial factors and managers' and colleagues' knowledge and acceptance of MBP; and (4) the need for structural changes, including future recommendations on quality assessment and guidelines. Conclusion: This study highlights the need for national guidelines for MBP provision and teacher training pathways, as well as improved availability of teacher training. Also, the benefit of a stepped-care model of MBP provision is indicated by the findings. Finally, increasing awareness of MBPs among referrers, managers, and the public may enable successful implementation.